Hydrological change effects on Sungai Langat Water quality - Marina Zainal Abidin,; Ahmad Abas Kutty,; Tukimat Lihan,; Nurul Akhma Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study attempts to assess the impact of various types of land use along Sungai Langat and describes hydrological change and water quality variation along this river. This study also determines water quality of Sungai Langat based on low flow dry period Q100,7 using the application of QUAL2K. Dissolved oxygen (DO), pH, temperature and conductivity were measured in situ. Biochemical oxygen demand (BOD5), ammonia nitrogen (NH3-N) and total suspended solid (TSS) were analysed according to the standard methods (APHA). Water quality data was referred to National Water Quality Standards for Malaysia (NWQS) proposed by Malaysian Department of Environment (DOE) to estimate Sungai Langat water quality status. Four important water quality parameters namely DO, BOD5, NH3-N and TSS were simulated with QUAL2K version 2.07 for 83.67 km. As regard to individual parameter, DO classified this river into class III, BOD5 in Class II, NH3-N in Class IV and TSS in Class I. Based on QUAL2K simulation for low flow scenario, the results clearly demonstrates a gradually reduction of DO and BOD5 whereas NH3-N and TSS display opposite. Only NH3-N was found significantly increase which cause low water quality class towards the downstream. Three parameters namely DO, BOD5 and NH3-N show effects of industrial which approximately located at the middle of river stretch. The TSS was contributed to the river system at the upstream and downstream of the river stretch which most likely from sand mining activity which located at Sungai Long, Cheras (near R5) and Sungai Semenyih (R11).